Blueshift of the optical bandgap in ZnO films by controlling the substrate temperature - Nurfani, Eka; Chotimah, Cindy; Anrokhi, M.S.; Kadja, G.T.M.; Sipahutar, W.S.; Mustaqim, A.; Rianjanu, A. (Jurnal Fisika dan Aplikasinya, 2025)
This study investigates the growth of ZnO thin films using the spray pyrolysis method, focusing on the effect of substrate temperature on the optical bandgap. By varying the deposition temperature from 300 to 500 °C, we aim to understand how temperature influences the optical properties of ZnO films. The films were characterized using X-ray diffraction (XRD) and UV-visible spectroscopy (UV-Vis). At 300 °C, the absorption was lowest, and the optical bandgap increased from 3.20 eV at 300 °C to 3.70 eV at 500 °C. These findings are crucial for developing ZnO materials for optoelectronic applications using an efficient and cost-effective deposition method.